Аналіз результатів синтезу шестиланкових механізмів четвертого класу з наближеним вистоєм вихідної ланки - Зінченко, Олена Іванівна (НТУ "ХПІ", 2008)
In the article method of kinematics synthesis of six-link mechanisms of fourth class with the initial stop of driven link in one of final positions are considered. The results of synthesis and their analysis are considered
Keywords: повзун; шарніри; коромисло; кривошип; статика; швидкість